Study on calculation method of auxiliary materials for transmission tower. Issue 1 (June 2020) - Fu, Benzhao; Yu, Xinmin; Xie, Ming
Abstract: Comparing the provisions of domestic and foreign codes on the supporting force of auxiliary materials, the major domestic design institutes used design software, combined with the test results of the 220kV double-circuit linear tower (SZ801) true-type test, and concluded that compared with "Standard for design of steel structures", "Design of latticed steel transmission structures "and the test results, the value of the internal force of the auxiliary materials of "Technical code for the design of tower and pole structures of overhead transmission line "is conservative. The value of the internal force of auxiliary materials supported by "Industry standards" only considers the influence of the main and inclined materials, and does not consider the effect of different equal distribution methods on the value.